Development of a Four-Tier Diagnostic Instrument to Identify High School Students' Understanding of Salt Hydrolysis - Anne Nailul Aziz; Darsono Sigit (PT Ahan Group Publisher, 2025)
This research aims to (1) produce a four-tier instrument in salt hydrolysis, (2) determine the validity and reliability of the instrument to facilitate students' understanding of salt hydrolysis. The development of the instrument followed the platform developed by Habiddin & Page (2019), which was adapted from the Treagust (1988), which consisted of six steps. The results of instrument validation were 81.74% with a very feasible category, yielding 23 valid questions, with a reliability of 0.7985.